Współczesne koncepcje zarządzania w procesie integracji systemów zarządzania w organizacji zhierarchizowanej: Modern management concepts in the integration of management systems in hierarchical organizations - Wyrębek, Henryk (Management and Administration Journal, 2021)
Problems and new phenomena occurring in closer and further surroundings of enterprises make them rethink their situation and adapt to the new conditions. The impulses coming from the environment influence firms which have to model their interiors, change their structure and strategy, and integrate their systems of management. The integration of management systems permits comprehensive business management under a single cohesive system, whose basic task is to strive for the continuous improvement of the organization. The paper presents the possibilities of using modern management concepts in the integration of management systems.